2020
DOI: 10.3390/ijerph17093322
|View full text |Cite
|
Sign up to set email alerts
|

Association between Frequency of Breakfast Consumption and Insulin Resistance Using Triglyceride-Glucose Index: A Cross-Sectional Study of the Korea National Health and Nutrition Examination Survey (2016–2018)

Abstract: Diabetes mellitus is an important chronic disease causing economic and social burden. Insulin resistance is a determinant of diabetes, and regular eating patterns are an important factor in blood sugar control. This study investigated the association between breakfast frequency and the risk of increased insulin resistance in Koreans. Data for 12,856 participants without diabetes in the 2016–2018 Korea National Health and Nutrition Examination Survey were analyzed. Insulin resistance was assessed using the trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Kolb et al [46] reported detrimental consequences of prolonged high insulin concentrations and argues for a lifestyle that limits circadian insulin levels. Skipping breakfast a few times a week was associated with general adiposity and with general and central adiposity, as reported by Wadolowska et al [47], and was also associated with a higher risk of insulin resistance, as data from Joo et al [48] showed. Consuming a three-meal diet with a carbohydrate-rich breakfast allows insulin dose reduction, leading to weight loss and better glycemic control compared with an isocaloric six-meal diet, as reported by Jakubowicz et al [49].…”
Section: Bmi Is Not the Main Driver For Insulin Resistance; Insulin Resistance Drives Bmisupporting
confidence: 55%
See 1 more Smart Citation
“…Kolb et al [46] reported detrimental consequences of prolonged high insulin concentrations and argues for a lifestyle that limits circadian insulin levels. Skipping breakfast a few times a week was associated with general adiposity and with general and central adiposity, as reported by Wadolowska et al [47], and was also associated with a higher risk of insulin resistance, as data from Joo et al [48] showed. Consuming a three-meal diet with a carbohydrate-rich breakfast allows insulin dose reduction, leading to weight loss and better glycemic control compared with an isocaloric six-meal diet, as reported by Jakubowicz et al [49].…”
Section: Bmi Is Not the Main Driver For Insulin Resistance; Insulin Resistance Drives Bmisupporting
confidence: 55%
“… 47 , and was also associated with a higher risk of insulin resistance, as data from Joo et al. 48 showed. Consuming a three-meal diet with a carbohydrate-rich breakfast allows insulin dose reduction, leading to weight loss and better glycemic control compared with an isocaloric six-meal diet, as reported by Jakubowicz et al.…”
Section: Introductionmentioning
confidence: 76%
“…Nevertheless, some studies indicate an absence of connection between breakfast skipping and obesity, while others suggested that breakfast skipping could lead to body weight loss [ 22 , 23 ]. Furthermore, breakfast skipping was linked with an elevated risk of many diseases, such as depression, cardiovascular diseases, diabetes mellitus, and some cancers [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of exposure assessment, most epidemiological studies have characterized meal-timing through questionnaires and have tended to analyse single meal-timing aspects, e.g. dinner time [10] or breakfast skipping [15][16][17][18][19][20]. However, different meal-timing aspects, such as nighttime fasting interval, interval between the last eating occasion and bed time or breakfast skipping, are interrelated and their effects could overlap.…”
Section: Introductionmentioning
confidence: 99%